Dissociating Cognitive Processes During Ambiguous Information Processing in Perceptual Decision-Making - Maksimenko, Vladimir A.; Kuc, Alexander; Frolov, Nikita S.; Khramova, Marina V.; Pisarchik, Alexander N.; Hramov, Alexander E. (Frontiers in Behavioral Neuroscience, 2020)
Decision-making requires accumulating sensory evidence. However, in everyday life, sensory information is often ambiguous and contains decision-irrelevant features. It requires the brain to disambiguate sensory input and extract decision-relevant features. The sensory information processing and decision-making represent two subsequent stages of the perceptual decision-making process. While sensory processing relies on the occipito-parietal neuronal activity during the earlier time window, decision-making lasts for a prolonged time involving parietal and frontal areas. Although perceptual decision-making is actively studied, its neuronal mechanisms under the ambiguous sensory evidence lack detailed consideration. Here, we analyzed the brain activity of subjects accomplishing a perceptual decision-making task involving ambiguous stimuli classification. We demonstrated that ambiguity induced high frontal $θ$-band power for 0.15~s post-stimulus onset, indicating increased reliance on top-down processes such as expectations and memory. Ambiguous processing also caused high occipito-parietal $β$-band power for 0.2~s and high fronto-parietal $β$-power for $0.35-0.42$~s post-stimulus onset. We supposed that the former component subserved the disambiguation process, while the latter one reflected the decision-making phase. Our findings complemented the existing knowledge about the ambiguous perception by providing additional information regarding the temporal discrepancy between the different cognitive processes during the perceptual-decision making.